The Three Good Things Intervention to Increase Subjective Well-Being in Students SMK PGRI Jatinangor - Irientania Azizah Putri; Mia Chandra Dewi; Fanisa Tsabila Hanum; Dyane Riri Arita; Fitri Ariyanti Abidin (Didaktika: Jurnal Kependidikan, 2024)
Adolescence is a transitional period that is complex and full of emotional conflicts. This study aims to determine whether the three good things intervention can improve subjective well-being in adolescents. The participants were 38 students of SMK PGRI Jatinangor, Satisfaction With Life Scale (SWLS), and Positive and Negative Affect Schedule (PANAS) were used to measure the students' subjective well-being and then analyzed using paired sample t-test. The results show that there is no difference in subjective well-being within the experiment group who get the three good things intervention after and before. Thus, it can be inferred that there is no significant effect of the three good things intervention on subjective well-being in adolescents.